Detection and identification of crystals in synovial fluid - F. Oliviero; E. Pascual; L. Punzi (PAGEPress Publications, 2011)
Synovial fluid analysis for crystals represents one of the most important laboratory test for the evaluation of rheumatic diseases. The identification of monosodium urate and calcium pyrophosphate dihydrate crystals allows the prompt diagnosis of gout and pyrophosphate crystal-related arthropaties. Crystals are identified based on their shape and birefringence through a polarized light microscope equipped with a first order red compensator. Due to its simple execution and high diagnostic value, this examine should be always performed to complete synovial fluid analysis.